Agroturismo, turismo sostenible y zonas ultraperiféricas: El caso de Canarias - Parra López, Eduardo; Calero García, Francisco (PASOS Revista de Turismo y Patrimonio Cultural, 2006)
Ultraperipheral regions share certain common characteristics, such as their remoteness from the major supplying centres, their scanty resources, their island status or isolated location and consequent fragmentation of markets. Over the past decades, there has been an increasing awareness of the impact of ultraperiphericity on the development of a number of regions and islands. The concept of “ultraperiphericity” includes specific geographic circumstances that influence the development and specialisation of economies, competitiveness and business strate- gies. Agrotourism is playing an ever increasingly important role in the diversification of the agriculture, farming and tourism sectors into the Ultraperipheral Regions. Therefore, particular attention should be paid to the economic development of rural areas in Ultraperipheral Areas and to the reappraisal of agriculture, which is closely connected with tourism. Agrotourism is essential to diversify, transform and improve the competitiveness and quality of farms. This paper examines the impact of Agrotourism as an alternative to sun and sand tourism, resulting in the growth of family income, in rural development and, in short, in new approaches to the tourism industry. A further goal of the paper is to develop a strategic analysis of Agrotourism, studying both supply and demand in the Canary Islands.